THE CIRC TECHNIQUE IN TEACHING READING COMPREHENSION ON DESCRIPTIVE TEXT - Lita Legiawati (Journal of English Education Program (JEEP), 2017)
This paper deals with the analysis of the CIRC technique in teaching reading comprehension on descriptive text. This study was aimed at investigating how the teacher apply CIRC technique in teaching reading descriptive text and the students’ perception on the way of CIRC technique applied by the teacher of reading descriptive  text. The basic theory of CIRC technique itself was from Slavin  (2005). The writer used a case study design as a research design of the study in order to gained the detail information the CIRC technique in teaching reading comprehension on descriptive text. The population in this study was the entire English teachers and all of the students at the eleveth grade in one of the senior high school in Ciamis consisted of four English teacher and 253 students. The sample was an English teacher and 30 students. The instruments used in this study consisted of three instruments including classroom observation, questionnaire and interview. The results of data analysis showed that the teacher has implemented the elements of CIRC technique including basic activity, direct teaching, and language art (David, 2002, p. 12. In conclusion,  the implementation of CIRC technique was effective in motivating and enjoying the students during the teaching and  learning process. The study suggested to the English teacher, the students and also the researcher for further study. Besides, their further researchers are suggested to use various research instruments to gain the richer data.